Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan di Kabupaten Padang Lawas - Aulia Ramadani, Putri; Taufik, Taufeni; Nurulita, Suci (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This study considers key factors that have the potential to affect the quality of financial statements which include human resource competence, accounting information systems, internal control systems, leadership styles and organizational commitments by focusing on all OPDs in Padang Lawas district. The phenomenon that occurred was that Padang Lawas Regency received a WDP opinion for FY 2022. The population in this study is all OPDs in PadangLawas Regency.The population in this study is all OPDs in Padang Lawas Regency. The sampling technique in this study uses the purposive sampling method and samples were obtained in this study as many as 28 OPDs in Padang Lawas Regency. The data used in this study is primary data, namely by using a questionnaire as a data collection tool. The data analysis technique in this study uses validity tests, reliability tests and hypothesis tests with the help of the Structural Equation Modeling (SEM). The results of this study show that the variables of Human Resources Competence, Internal Control System and Organizational Commitment have an effect on the Quality of Financial Statements. This shows that the level of compliance with accounting standards is high. Meanwhile, the variables of Accounting Information System and Leadership Style have no effect on the Quality of Financial Reports in OPDs in Padang Lawas Regency. Because maybe the brainware in OPD is still weak or less than optimal